A new framework for advancing in drug-induced liver injury research. The Prospective European DILI Registry. - Bjornsson, Einar S.; Stephens, Camilla; Atallah, Edmond; Robles-Díaz, María Mercedes; Álvarez-Álvarez, Ismael; Gerbes, Alexander L; Weber, Sabine; Stirnimann, Guido; Kullak-Ublick, Gerd A; Cortez-Pinto, Helena; Grove, Jane I.; Lucena-González, María Isabel; et al. (Wiley, 2023)
Background & Aims: No multi-national prospective study of drug-induced liver injury (DILI) has originated in Europe. The design of a prospective European DILI registry, clinical features and short-term outcomes of the cases and controls is reported. Methods: Patients with suspected DILI were prospectively enrolled in the United Kingdom, Spain, Germany, Switzerland, Portugal and Iceland, 2016–2021. DILI cases or non-DILI acute liver injury controls following causality assessment were enrolled. Results: Of 446 adjudicated patients, 246 DILI patients and 100 had acute liver injury due to other aetiologies, mostly autoimmune hepatitis (n = 42) and viral hepatitis (n = 34). DILI patients (mean age 56 years), 57% women, 60% with jaundice and 3.6% had pre-existing liver disease. DILI cases and non-DILI acute liver injury controls had similar demographics, clinical features and outcomes. A single agent was implicated in 199 (81%) DILI cases. Amoxicillin-clavulanate, flucloxacillin, atorvastatin, nivolumab/ipilimumab, infliximab and nitrofurantoin were the most commonly implicated drugs. Multiple conventional medications were implicated in 37 (15%) and 18 cases were caused by herbal and dietary supplements. The most common single causative drug classes were antibacterials (40%) and antineoplastic/immunomodulating agents (27%). Overall, 13 (5.3%) had drug-induced autoimmune-like hepatitis due to nitrofurantoin, methyldopa, infliximab, methylprednisolone and minocycline. Only six (2.4%) DILI patients died (50% had liver-related death), and another six received liver transplantation. Conclusions: In this first multi-national European prospective DILI Registry study, antibacterials were the most commonly implicated medications, whereas antineoplastic and immunomodulating agents accounted for higher proportion of DILI than previously described. This European initiative provides an important opportunity to advance the study on DILI.
Keywords: Hígado - Enfermedades; Efectos indeseables de los medicamentos; Vigilancia epidemiológica; Drug aetiologies; Drug-induced autoimmune-like hepatitis; Drug-induced liver injury; Outcomes; Prospective study